Odpowiedzi

2010-01-07T19:40:39+01:00
A) (x+7)(2x-1)
2x [kwadrat] - x + 14x - 7 = 13x + 2x [kwadrat] - 7


b) (2a-1)(a+4)
2a [kwadrat] + 8 a - a - 4 = 7a + 2a [kwadrat] - 4


c) (4a-1)(2-3a)
8a - 12 a [kwadrat] - 2 + 3a = 11a - 12a [kwadrat] - 2
2010-01-07T19:42:41+01:00
A)=2x^-x+14x-7=2x^+13x-7
b)=2a^+8a-1a-4=2a^+7a-4
c)=8a-12a^-2+3a=11a-12a^-2

Legenda

^= do potęgi drugiej
2010-01-07T19:51:02+01:00
A) (x+7)•(2x-1)=x•(2x-1)+7•(2x-1)=2(x^2)-x+14x-7=2(x^2)+13x-7
Wynik - 2(x^2)+13x-7

b) (2a-1)•(a+4)=2a•(a+4)-a+4=2(a^2)+8-a+4=2(a^2)+12-a
Wynik - 2(a^2)+12-a

c) (4a-1)•(2-3a)=4a•(2-3a)-2-3a=8a-12(a^2)-2-3a=5a-12(a^2)-2
Wynik - 5a-12(a^2)-2